Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Konsumen melalui Marketing Relationship di Masa Pandemi Covid-19 - Rachmawati, Ike Kusdyah (University of Merdeka Malang, 2021)
Competition in providing the best service needs to be done to pamper and give satisfaction to customers, this can be realized by providing something more for customers to enjoy the food and drinks offered even during the current pandemic. This research is quantitative descriptive. This study took service quality and product quality as the independent variables, consumer satisfaction as the dependent variable, and relationship marketing as the intervening variable. The research location is CafÃ© BataPuti Coffee House. The population in this study were people who had visited CafÃ© BataPuti. The sample used is as many as 90 respondents to people who have visited the BataPuti Coffee House. The analysis used is Path Analysis Analysis. The results of this study is a significant impact on relationship marketing toward service quality and product quality. service quality and product quality have a significant effect on consumer satisfaction. service quality on customer satisfaction through relationship marketing has a significant effect. Product quality on consumer satisfaction through relationship marketing has a significant effect.